Gambaran Ideasi Bunuh Diri - Wulandari, Mike; pradessetia, reski (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Suicide has become an increasingly prominent issue in recent years, but there has been little attention to this phenomenon in the elderly, especially in the media. Reports show that elderly people in Indonesia often choose hanging themselves as a method to end their lives. This study aims to determine the description of suicidal ideation in the elderly. The approach used was quantitative with a cross-sectional survey design. Data were collected using the Geriatric Suicide Ideation Scale (GSIS) based questionnaire, which uses a four-point Likert Scale. The research was conducted in the working area of Puskesmas Pekanbaru with proportional random sampling technique, involving 60 respondents. The results showed that elderly women had a suicide risk of 25% compared to men 17%. A total of 67% of respondents were not at risk of suicidal ideation, while 43% were at risk. The findings provide initial insight into the distribution of suicidal ideation in the elderly for more appropriate interventions.